The mirror and the lamp: Romantic theory and the critical tradition - Abrams, M. H. (London Oxford university press, 1971)
In a powerful contrast, Abrams shows that until the Romantics, literature was usually understood as a mirror, reflecting the real world, in some kind of mimesis; but for the Romantics, writing was more like a lamp: the light of the writer's inner soul spilled out to illuminate the world.